Controle de convencionalidade sob a abordagem da transjuridicidade no sistema interamericano de proteção dos direitos humanos - Lima Sobrinho, Luis Carlos dos Santos (2017)
The present study, which is of an applied nature, qualitative approach, deductive method as well as of exploratory focus, relies on technical procedures such as bibliographical and documentary research and also on content analysis in order to survey about the use of the conventionality control in the Inter-American background in accordance with the common tools that are attached to the juridical interculture. Initially, issues – like justiciability and functionality of paradoxes, interaction models and normative integration, and considerations about the concept of human rights which are the basis for both general and regional protection and promotion systems – are enclosed. There has to be the understanding that the consolidation of such judicial systems refers to the fulfilling of risen fundamental rights and freedoms, problems – resulted from incompatibility between internal and international rights’ rules – are identified. This fact mostly undermines the effectiveness of their precepts, illustrating the operational sphere of the conventionality control, then, explaining its improvement. Under the transjuridicity approach, it starts with the hypothesis that this appeal can be strategically effected with the establishment of new interaction ways between States and management organizations, by surpassing the common restrictions in relation to jus-positivistic models and functionalistic patterns expanding their performance specter and normative exchanges that result from the understanding of more proper techniques and procedures as to the transnational context of human rights’ protection, while regarded as compatibility parameters which unite the performance of all agents and organs of jurisdictional trait, the right and conventional jurisprudence can see their effects enhanced in a background of plurality and interconnection of juridical orders and of globalization of the cognitive processes which enclose aspects such as transconstitutionalism, global government ship, net theory, dialogues between judges and Courts, judicial activism, judicial borrowing and legal transplants, among others. Along with well-known national and foreigner scientific works, the main rules are interpreted. These ones constitute a kind of juridical body of common Inter-American right, as well as the emblematic cases that are judged by the respective regional Court in the exercise of its competence. Having as underlying issues conventional regime and contentious jurisdiction, the normative integration and the effectiveness of fundamental rights and freedoms, the legitimating and the exercise of the conventionality control, general repercussion of the conventional right and anti-conventionality, expansion of the conventional law and the jurisdictional interaction, a series of imposed condemnations, towards the States that are part of the Inter-American System of Human Rights, is identified as a result of the non-incorporation of these precepts to its justice management organs. In relation to Brazil, which, again, can be charged due to the existence of open judgment cases before the Inter-American Court of Human Rights. Furthermore, what is observed is the material insufficiency in the performance of its Supreme Court, which is commonly limited to mention scarce – and totally disconnected about the issue – judged foreigners. As social justice action and change of theoretical-practical paradigms in the social and academic context, this study gets to the conclusion about the imprescindibility of the conventionality control under the transjuridicity approach, by taking for granted the rules of law of the whole efficiency, the immediate applicability, the progressiveness and the prevalence of the more favorable regulation for human dignity in the transnational background.